TRANSLATION METHODS AND TECHNIQUES A TRANSLATION STUDY FROM ENGLISH TO INDONESIAN - Nasya Rizki Nabilah; Meita Lukitawati Sujatna (English Journal Literacy Utama, 2020)
This study is entitled "Analysis of Translation Methods and Techniques in the Novel Curse of the Wendigo by Rick Yancey. Study: Translation ". The data source used is a novel titled the Curse of the Wendigo by Rick Yancey. The objectives of this research are to (1) identify the translation method used in the translation of the novel The Curse of the Wendigo by Rick Yancey. (2) identify the types of translation techniques used in the translation of Rick Yancey's novel The Curse of the Wendigo. (3) identify the relationship between the translation methods and techniques used in the translation of Rick Yancey's novel The Curse of the Wendigo. The method used in this research is a qualitative descriptive approach. The theoretical basis of this research is the theory of the Newmark translation method (1988) and the Molina & Albir (2002) translation techniques. The results of this study indicate that there are: (1) seven translation methods used, namely literal (3.2%), faithful (3.2%), semantic (45.2%), adaptation (3.2%) ), idiomatic (3.2%), free (9.7%), and communicative (32.3%). (2) 17 translation techniques used are adaptation (1.2%), amplification (2.4%), borrowing (3.5%), calculating (2.4%), compensation (1.2%), description (2.4%), prevalent equivalent (3.5%), generalization (2.4%), linguistic amplification (9.4%), linguistic compression (17.6%), literal (20%), modulation ( 7.1%), particularization (2.4%), reduction (1.2%), substitution (1.2%), variation (3.5%), and transposition (18.8%). (3) six of the seven translation methods related to the translation technique used.